Conductometric Study of Complexation of Some Transition Metal Cations with 1,10-Phenanthroline, 2,2’-Bipyridine and 8-Hydroxyquinoline in Acetonitrile Solution - Hasani, Masoumeh; Afkhami, Abbas (Asian Journal of Chemistry, 2010)
Complexation of Mn2+, CO2+, Ni2+, Cu2+, Zn2+ and Cd2+ with 1,10- phenanthroline, 2,2'-bipyridine and 8-hydroxyquinoline in acetonitrile has been studied conductometrically at 25°C. The stoichiometry and stability constants of the resulting complexes were evaluated from nonlinear least -square fitting of the conductometric data to appropriate equations. The stabilities of the resulting complexes vary in the order of phen > bipy > oxine.